PENERAPAN MODEL PEMBELAJARAN PROBLEM BESED LEARNING UNTUK MENINGKATKAN KEMAMPUAN BERFIKIR KRITIS SISWA KELAS 3 MI TARBIYATUL ISLAM - Qomaria, Putri Lailatul; amalia, Nur fitri (ELEMENTARY : Journal of Primary Education, 2023)
This research aims to determine the improvement in critical thinking skills and student learning outcomes when the Problem Based Learning model is applied to B.Indonesia learning about animal and plant fairy tales. This research is classroom action research which was carried out in two cycles and each cycle was carried out in two meetings. The subjects of this research were class III students at MI Tarbiyatul Islam. Data from this research were obtained from tests, observations and field notes. The results of this research show an increase in critical thinking skills from 63.49% in cycle I and Increased to 76.96% in cycle II. The results of studying classical attitudes were from 57.62% in cycle I and increased to 78.32% in cycle II . Knowledge learning outcomes increased during two learning cycles, in cycle I it was 54.62%, in cycle II it increased to 89.58%. Skills learning outcomes increased from 47.38% in the first cycle to 68.89% in the second cycle.